Pelatihan Dasar Editing Video dan Desain Grafis Guru PAUD Karangroto Semarang - Hasanah, Nida Ul; Ardhani, Muhammad Chabibul; Alhammam, Muhammad Yusron; Sadad, Roihan; Huda, Nuril; Wijayanti, Linda Dwi; Aini, Aniswa Miladi Qurrota; Nikmah, Itiqoul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Amidst the challenges of technological development facing the world of education today, early childhood education teachers have their challenges where teachers need to choose learning media that can stimulate early childhood interest in learning. With these problems, the efforts made are to provide training in making teaching videos using the Capcut application and making graphic designs using the Canva application. This training aims to simplify and make the learning process more effective and can make the learning process more interesting for early childhood. Community service activities are carried out using the Participatory Action Research (PAR) approach which focuses on community empowerment. Based on the results of the evaluation of the questionnaire distributed to PAUD teachers, this activity has succeeded in increasing the knowledge and skills of participants, especially PAUD teachers in the basic fields of video editing and graphic design.